Strategic Leadership Dimensions and Their Effect on Learning Organizations - Aram Taha Muhammad Salih (Studi Akuntansi dan Bisnis Indonesia, 2026)
Purpose: This study examines the influence of strategic leadership on the process of building learning organizations within the higher education sector, drawing on a field investigation carried out at Kirkuk University. The dimensions of strategic leadership addressed in the study are human capital, ethical practices, organizational culture, and strategic vision, while the dimensions of the learning organization consist of shared vision, leadership, learning, and change.Research Methodology: A descriptive-analytical approach was adopted, and a structured questionnaire was distributed to 120 administrative and academic leaders, including deans, assistant deans, heads of departments, and directors of divisions and units. Data normality was verified before applying parametric statistical procedures through SPSS version 26.Results: The findings indicate a positive and statistically significant correlation between strategic leadership and learning organizations, and every dimension of strategic leadership was found to exert a significant effect on learning organizations, with strategic vision emerging as the strongest predictor.Conclusions: Strengthening strategic leadership practices contributes meaningfully to the transformation of universities into learning organizations.Limitations: The cross-sectional design and the single-institution sample restrict the generalizability of the findings.Contributions: The study extends the strategic leadership literature within an Iraqi higher education context and offers practical guidance for university administrators seeking to cultivate organizational learning.